(untitled) - Gosselin, Don (Australia, 2001)
This text book is 640 pages and does not come with CD. C++ is a 3-dimensional morass of subjects and related subjects: intro to the VC++ compiler, C++ Basics, Operators & Control Structures, Memory Management & Classes, Object Manipulation (more class work), and Inheritance.
Keywords: C++ (Computer program language),C++ (Ngôn ngữ chương trình máy tính)